2015
DOI: 10.1007/s12602-015-9192-8
|View full text |Cite
|
Sign up to set email alerts
|

A Moonlighting Enolase from Lactobacillus gasseri does not Require Enzymatic Activity to Inhibit Neisseria gonorrhoeae Adherence to Epithelial Cells

Abstract: Enolases are generally thought of as cytoplasmic enzymes involved in glycolysis and gluconeogenesis. However, several bacteria have active forms of enolase associated with the cell surface and these proteins are utilized for functions other than central metabolism. Recently, a surface-associated protein produced by Lactobacillus gasseri ATCC 33323 with homology to enolase was found to inhibit the adherence of the sexually transmitted pathogen, Neisseria gonorrhoeae, to epithelial cells in culture. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Bioactivity of several molecules that we identified in HIV-1-inhibiting EVs was reported earlier: several enolases derived from Lactobacillus were shown to inhibit the adherence of Neisseria gonorrhoeae to epithelial cells 34 . Moreover, bifidobacterial enolase, a cell-surface receptor for human plasminogen, was involved in interaction with human host cells 35 .…”
Section: Discussionsupporting
confidence: 65%
“…Bioactivity of several molecules that we identified in HIV-1-inhibiting EVs was reported earlier: several enolases derived from Lactobacillus were shown to inhibit the adherence of Neisseria gonorrhoeae to epithelial cells 34 . Moreover, bifidobacterial enolase, a cell-surface receptor for human plasminogen, was involved in interaction with human host cells 35 .…”
Section: Discussionsupporting
confidence: 65%
“…In the fungal pathogen Aspergillus fumigatus , enolase also acts as a virulence factor in recruiting human regulators ( 53 ), and in Trichomonas vaginalis , enolase plays a role in virulence by activating plasminogen to plasmin ( 54 ). Interestingly, some commensal bacteria, including L. johnsonii, L. crispatus and L. plantarum , also encode enolases that can bind plasminogen and activate plasmin ( 55 ), among other moonlighting activities. A surface-associated protein homologous to enolase (Eno3) from L. gasseri ATC 3323 was found to inhibit the adherence of Neisseria gonorrhoeae to epithelial cells ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some commensal bacteria, including L. johnsonii, L. crispatus and L. plantarum , also encode enolases that can bind plasminogen and activate plasmin ( 55 ), among other moonlighting activities. A surface-associated protein homologous to enolase (Eno3) from L. gasseri ATC 3323 was found to inhibit the adherence of Neisseria gonorrhoeae to epithelial cells ( 55 ). Similar to L. gasseri ATCC 33323, L. johnsonii N6.2 also has three enolase genes, and our results support the surface localization of Eno3 in L. johnsonii N6.2.…”
Section: Discussionmentioning
confidence: 99%
“…To expand our consideration of species-specific differences and explore a potential environment in which DTZ would be clinically useful (the lower female reproductive tract), we tested the efficacy of DTZ against a representative vaginal commensal, Lactobacillus gasseri. L. gasseri has been previously shown to block N. gonorrhoeae-epithelial cell interactions (28,29), and lactobacilli in general maintain a low pH in the vagina that is an important determinant of discouraging Neisseria growth (30). We found that L. gasseri is greatly reduced in sensitivity to DTZ compared to that of N. gonorrhoeae as well as the previously described E. coli and Salmonella enterica (17).…”
mentioning
confidence: 49%